4x*2c-4+4c=0

Simple and best practice solution for 4x*2c-4+4c=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x*2c-4+4c=0 equation:


Simplifying
4x * 2c + -4 + 4c = 0

Reorder the terms for easier multiplication:
4 * 2x * c + -4 + 4c = 0

Multiply 4 * 2
8x * c + -4 + 4c = 0

Multiply x * c
8cx + -4 + 4c = 0

Reorder the terms:
-4 + 4c + 8cx = 0

Solving
-4 + 4c + 8cx = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4c + 4 + 8cx = 0 + 4

Reorder the terms:
-4 + 4 + 4c + 8cx = 0 + 4

Combine like terms: -4 + 4 = 0
0 + 4c + 8cx = 0 + 4
4c + 8cx = 0 + 4

Combine like terms: 0 + 4 = 4
4c + 8cx = 4

Reorder the terms:
-4 + 4c + 8cx = 4 + -4

Combine like terms: 4 + -4 = 0
-4 + 4c + 8cx = 0

Factor out the Greatest Common Factor (GCF), '4'.
4(-1 + c + 2cx) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(-1 + c + 2cx)' equal to zero and attempt to solve: Simplifying -1 + c + 2cx = 0 Solving -1 + c + 2cx = 0 Move all terms containing c to the left, all other terms to the right. Add '1' to each side of the equation. -1 + c + 1 + 2cx = 0 + 1 Reorder the terms: -1 + 1 + c + 2cx = 0 + 1 Combine like terms: -1 + 1 = 0 0 + c + 2cx = 0 + 1 c + 2cx = 0 + 1 Combine like terms: 0 + 1 = 1 c + 2cx = 1 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| t(p)=(ln(p/25))/.12 | | 2z+8-9=-30.5 | | m+3-(2)=7 | | .6n+4=18 | | 8x=x-2 | | (-9x-3).2/3 | | r^2-16r+15=0 | | 34x+3+96+59x+75=360 | | 9k+3=12k | | 130+48+14x=360 | | 2w+7=16 | | 42j+19j-18=28 | | 9x-3+30=90 | | n^2-10n-39=0 | | (2x-1)(x+8)=2x^2+15x-8 | | 5sin^2a-5sin^4a=5cos^2a-5cos^4a | | 8+14x-7=7x+56-4x | | Z-7=1+2Z | | 6t=-21 | | 2Y+9=10Y | | 6x+9=rx+t | | x(90-x)=18 | | -22.5=7k-5.5k | | x+60-y-10=180 | | 3=x/-3-1 | | 2*(7/4)^2-7(7/4)-4 | | 15=7x-5(2x+3) | | 39=3(x+2) | | -3n-4+2n=-27 | | 29+12x=173 | | 198=-6(-6-3) | | 12x-20=-4x-16 |

Equations solver categories